The Role of the Group Process System Approach in Optimizing Learning Management - Jelita Ayu Melani; Masduki Asbari; Fitria Eriyanti Putri (Journal of Information Systems and Management (JISMA), 2023)
This study aims to analyze group processes' practice in optimizing learning management. This study report was carried out using a descriptive qualitative method by reviewing scientific articles taken from Google Scholar taking Scholarhe results of the study, that the group process in optimizing learning management requires good classroom management, and as a class manager, the teacher is a figure who has a strategic role because he is the planner of various activities that will be carried out in class. To be able to implement the planned activities, of course, he must determine, alternatives as solutions to various obstacles and challenges that arise. One approach that can be used to optimize classroom management is the group process system approach, namely the approach used by teachers to improve and maintain class groups to remain effective and productive.